CULTURE AS A WAY OF INTERACTION WITH NATURE - Skyba, Ivan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. In recent decades, society's attention to nature has increased significantly. First of all, this is due to a dramatic growth of environmental problems. The search for ways to solve existing problems in the system of nature leads to an awareness of the relationship between the state of ecology and the specifics of the socio-cultural development of society, thus updating various studies aimed at identifying the specifics of culture and nature. The aim and tasks are a socio-philosophical study of culture as a way of interacting with nature. Research methods. The methodological strategy of the research is based on socio-cultural, cultural-historical, systemic, and comparative methodological approaches in their dialectical relationship. Research results. The study of the essence of culture inevitably encounters antinomy: that is, the contradiction between two judgments that are recognized as true. On the one hand, culture is supernatural, and non-biological, it cannot be reduced to the natural. On the other hand, the cultural is being constructed out of the natural, nothing more. In this way, the impression of the simultaneous unity and difference between cultural and natural is created. This perspective of the study implies in the long run a need to take into account both points of view. It leads to the recognition of parity, not a priority in understanding the strategy of culture and nature. The key to solving this problem, according to the author, lies in the anthropological plane, because it is the man who actively influences the interaction of culture and nature, combining the two systems because it belongs internally to each of them. Discussion. The historical development of the concept of "culture" in the context of its relation to the concept of "nature" is considered in the discussion. Conclusion. Since culture is a way of human interaction with nature, its specificity largely determines the state of affairs in nature. Exit from crisis situations implies corresponding changes both in the anthropological and socio-cultural plane.